Peran Lingkungan Sekolah Dalam Meningkatkan Prestasi Belajar Peserta Didik - Qori Istiqomah Apriliana; Ellen Prima (Pascasarjana Universitas PGRI Semarang, 2026)
The school environment has an important role in supporting the success of students’ learning processes. This study aims to identify the meaning of the school environment, the role of the school environment in improving students’ learning achievement, the factors influencing learning achievement, and the efforts to create a conducive school environment. The research employed a descriptive qualitative method with data collection techniques through literature study from various relevant sources. The results of the study indicate that a safe, comfortable, clean, and supportive school environment can improve students’ motivation, concentration, and learning achievement. In addition, adequate school facilities, interactive teaching methods, and cooperation between schools and parents also provide positive impacts on students’ academic development and character building.